Variation in Structure and Process of Care in Traumatic Brain Injury: Provider Profiles of European Neurotrauma Centers Participating in the CENTER-TBI Study - Cnossen, MC; Polinder, S; Lingsma, HF; Maas, AIR; Menon, D; Steyerberg, EW; Curry, N; Stanworth, S; Keeling, D; CENTER-TBI Investigators and Participants (Public Library of Science, 2016)
Introduction: The strength of evidence underpinning care and treatment recommendations in traumatic brain injury (TBI) is low. Comparative effectiveness research (CER) has been proposed as a framework to provide evidence for optimal care for TBI patients. The first step in CER is to map the existing variation. The aim of current study is to quantify variation in general structural and process characteristics among centers participating in the Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury (CENTER-TBI) study.